FRI0421 Toll like receptor-7/8 activation exacerbates murine experimental autoimmune myositis. (12th June 2018) - De Lorenzo, R.; Sciorati, C.; Monno, A.; Doglio, M.G.; Rigamonti, E.; Ascherman, D.; Manfredi, A.; Rovere-Querini, P.
Abstract : Background: Type I interferon (IFN)-regulated proteins are upregulated in muscle and skin tissues of patients with idiopathic inflammatory myopathies (IIM). 1 Type I IFN induction might rely upon the activation of toll-like receptors (TLRs). 2 Specifically, TLR-7/8 is indeed upregulated in infiltrating leukocytes and muscle tissue of IIM patients. 3 Objectives: To investigate whether the activation of TLR-7/8 and type I IFN influences the natural history of the IIM. Methods: Experimental autoimmune myositis (EAM) was induced by injection of the amino-terminal portion of the murine Histydil t-RNA synthetase (HisRS). Disease activity was compared in the presence or absence of the TLR-7/8 agonist R848 in wild-type mice and in mice that failed to express the IFNab receptor (IFNabR null). Results: EAM induced by a single intramuscular immunisation with HisRS spontaneously abated after 7–8 weeks. In contrast, the levels of anti-HisRS autoantibodies, endomysial/perimysial leukocyte infiltration and myofiber regeneration persisted until the end of the follow-up period (22 weeks after immunisation) in mice immunised with HisRS in the presence of R848. Myofiber MHC class I molecules were detectable in HisRS +R848 immunised mice only. Muscle MHC expression occurred in parallel with leukocyte infiltration. Type I IFN was necessary for the prolonged autoantibody response to occur and for the spreading of the autoimmune response, as demonstrated using IFNabR null mice. Conclusions: TLR7/8 activation is needed to induce and maintain a systemic autoimmune response against the skeletal muscle. This EAM model reproduces many characteristics of human IIM and may represent a tool for pre-clinical studies. References: [1] Wenzel J, Scheler M, Bieber T, Tuting T. Evidence for a role of type I interferons in the pathogenesis of dermatomyositis. Br J Dermatol. 2005;153:462–463. [author reply 463–464] [2] Drexlerand SK, Foxwell BM. The role of toll-like receptors in chronic inflammation. Int J Biochem Cell Biol. 2010;42:506–518. [3] A. Tournadre, V. Lenief, A. Eljaafari, and P. Miossec. Immature muscle precursors are a source of interferon-beta in myositis: role of Toll-like receptor 3 activation and contribution to HLA class I up-regulation. Arthritis and rheumatism. 64:533–541 (2012). Disclosure of Interest: None declared